2003
DOI: 10.1007/s00383-002-0936-7
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and oestrogen receptor status of the human appendix testis

Abstract: Since the human appendix testis is a Mullerian duct derivative it has been theorised that rising oestrogen levels in puberty result in enlargement of this organ and consequent predisposition to torsion. This study sought to establish the presence or absence of both androgen and oestrogen receptors in the human appendix testis. Bilateral appendix testis specimens surgically excised from ten patients undergoing scrotal exploration for acute scrotum were stained immunohistochemically for androgen and oestrogen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
0
14
0
4
Order By: Relevance
“…Previous studies have shown that the testicular appendices of patients with cryptorchidism show significant alterations in the estrogen and androgen receptors (19,23). Patients with hydroceles also present alteration in the expression of androgen receptors and epithelial destruction in the testicular appendices (19).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that the testicular appendices of patients with cryptorchidism show significant alterations in the estrogen and androgen receptors (19,23). Patients with hydroceles also present alteration in the expression of androgen receptors and epithelial destruction in the testicular appendices (19).…”
Section: Discussionmentioning
confidence: 98%
“…Patients with hydroceles also present alteration in the expression of androgen receptors and epithelial destruction in the testicular appendices (19). These alterations are argued to be associated with increased hydrostatic pressure in the scrotum of patients with hydroceles (19,23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Samnakay et al [9] described that the human appendix testis was found to express both estrogen and androgen receptors. The significantly lower incidence of appendix testis in patients with undescended testes versus those with descended testes may suggest a physiological role of appendix testis, regulated by sexual steroids, in the process of testicular migration.…”
Section: Discussionmentioning
confidence: 99%
“…Appendiks testis torsiyonu: Testisin üzerinde apendiks testis (Morgagni; hidatid kisti), apendiks epididimis, paradidim, ve vas aberans adı verilen 4 adet Müllerien kanalın bir artıkları, preadolesan dönemdeki çocuklarda artmış olan östrojen hormonları etkisi ile büyür ve pedikülü etrafında kolayca dönebilir (5,16). Skrotumda, testisten ayrı ancak ona yapışık 0.5-1 cm.lik ağ-rılı bir kitle şeklinde ele gelir.…”
Section: Akut Skrotum Yapan Diğer Patolojilerunclassified